Translators censoring propaganda: a case study on the translation of Salazar’s speeches into English - Chumbo, Isabel (2014)
This study analyses translation as a support of propaganda during the dictatorial regime of António Oliveira Salazar (1932-68) in Portugal with particular emphasis on the 1930s and 1940s when many of the foundations of the regime were laid. The research is developed in two parts. First it investigates the relevance Salazar’s regime attributed to translation, mainly from Portuguese into English. Second it analyses a set of speeches by Salazar in order to understand how translators were influenced by the natural constraints of living and working in a dictatorship thus originating the occurrence of self-censorship